A Tomato-Free Period Delays and Reduces Begomovirus Disease in Processing Tomato Fields in a Complex Agroecosystem in Central Brazil - de Macedo, Mônica Alves (Plant disease, 2024)
A mandatory tomato-free period (TFP) was implemented in the state of Goiás, Brazil, in 2007 to help manage diseases caused by whitefly-transmitted begomoviruses. The impact of the TFP was examined in five locations across three states in Central Brazil from 2013 to 2016. Surveys revealed significant differences in begomovirus disease incidence among locations, i.e., low in Guaíra-TFP and Patos de Minas-TFP; moderate-high in Itaberaí-TFP and Morrinhos-TFP; and high in the non-TFP (NTFP) control, Cristalina-NTFP. PCR tests and DNA sequencing were used to validate the symptoms and showed that all collected symptomatic plant samples were infected with tomato severe rugose virus (ToSRV), a common indigenous bipartite begomovirus. Early season surveys (20 to 40 days after transplants [DAT]) in Itaberaí-TFP and Morrinhos-TFP revealed significantly less begomovirus disease in fields established sooner after the TFP (0 to 2 months) compared with incidences in (i) equivalent early planted fields in the Cristalina-NTFP control and (ii) fields established longer after the end of the TFP (>2 to 5 months). Whitefly infestation of crops was detected year-round in all locations and years, and all tested adults were classified in the Bemisia tabaci MEAM1 cryptic species. Infestation levels were significantly higher during the summer but did not vary significantly among locations. Results of monthly monitoring of adult whiteflies for general begomovirus and ToSRV were positively correlated and were indicators of disease incidence in the field. Notably, ToSRV was not detected in whiteflies collected from nontomato plants during the TFP, and there was a longer lag period before detection in whiteflies collected from processing tomatoes for Itaberaí-TFP and Morrinhos-TFP compared with Cristalina-NTFP. Taken together with the low levels of ToSRV infection detected in potential nontomato reservoir hosts at all locations, our results revealed low levels of primary inoculum during the TFP. Thus, even in a complex agroecosystem with year-round whitefly infestation of crops, the TFP was beneficial due to delayed and reduced begomovirus disease pressure during a critical stage of plant development (first month) and for favoring low levels of primary inoculum. Thus, we concluded that the TFP should be part of a regional integrated pest management (IPM) program targeting ToSRV in Brazil